Synthesis Strategies of Porous Carbon for Supercapacitor Applications. Issue 3 (12th February 2020) - Yin, Jian; Zhang, Wenli; Alhebshi, Nuha A.; Salah, Numan; Alshareef, Husam N.
Abstract: Supercapacitors (SCs) have experienced a significant increase in research activity and commercialization during the past few decades. As the primary and most important electrode active material for commercial SCs, porous carbon is produced at an industrial‐scale through traditional carbonization‐activation strategies. Nevertheless, commercial porous carbon materials have some disadvantages such as high production cost, corrosion of equipment, and emission of toxic gases and byproduct pollutants during production. In recent years, huge efforts have been made to develop novel synthesis strategies for porous carbon materials. This review focuses on the pore formation mechanisms in traditional carbonization‐activation methods, emerging activation methods, template methods, self‐template methods, and novel emerging methods for the synthesis of porous carbons for SCs. Strategies developed so far for the synthesis of porous carbon materials are summarized. The mechanisms and recent advances for each strategy are reviewed. Furthermore, future directions and synthesis strategies for porous carbons are proposed. Abstract : The synthesis strategies of porous carbon for supercapacitor (SC) applications, including traditional methods and novel emerging methods developed in recent years, are reviewed in this article. This review proposes promising future directions and synthesis strategies for porous carbons used in SC applications.